Advertising funded video-sharing platforms under the revised AVMSD: Commercial communication functionalities. (1st November 2021) - Broughton Micova, Sally; Kostovska, Ivana
The 2018 revision of the Audiovisual Media Services Directive (AVMSD) defined video-sharing platforms (VSPs) and brought them into the scope of the Directive, holding them responsible, though not liable, for preventing certain types of harm from both the user-generated content and the commercial communication they carry. The AVMSD introduces the concept of functionality to distinguish a platform as a VSP and bring it into scope. In this article, we present findings from an investigation that applied the concept of functionality more widely and sought to identify and understand those VSP functionalities relevant to commercial communications. We elaborate the creator-facing, advertiser-facing and user-facing functionalities found in a sample of thirteen VSPs by examining company documentation, and systematic testing through use, triangulated through semi-structured key informant interviews. Based on analysis of these commercial communications functionalities and the contractual relationships governing their use, we identify four purchasing pathways, each of which reveals roles played by stakeholders and distinct points of control. We therefore argue that the concept of functionality, which captures the platform design elements and the acceptance of a value proposition by various kinds of users, can be useful in distributing co-operative responsibility within dynamic, polycentric co-regulation and informing systems for enforcing procedural accountability.